Aluminum-copper alloy wire suitable for electric arc additive manufacturing and preparation method of aluminum-copper alloy wire
By regulating the content of trace alloy elements and adding Ce elements in aluminum-copper alloy wires, refining the grains and improving the uniform distribution of the reinforced phases, the problem of unstable mechanical properties in arc additive manufacturing of existing aluminum-copper alloy wires is solved, and high-efficiency, low-cost and high-performance aluminum-copper alloy arc additive manufacturing is achieved.
Patent Information
- Application Number
- CN202510102745.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-22
AI Technical Summary
In the arc additive manufacturing process of existing aluminum-copper alloy wires, the chemical composition and structure uniformity of existing aluminum-copper alloy arc additive forming components are poor, resulting in unstable mechanical properties of aluminum-copper alloy arc additive forming components, which is difficult to meet the needs of high efficiency, low cost and high performance manufacturing.
By adjusting the content of trace alloy elements in aluminum-copper alloy wire and adding purified grain boundary element Ce to form a dispersed distribution precipitation phase, refining the grains, and improving the uniform distribution of the reinforced phase, arc additive forming and solid solution quenching aging heat treatment process are used.
The composition and structure uniformity of aluminum-copper alloy wire is achieved, the tensile strength, yield strength and elongation are improved, plastic anisotropy is eliminated, and high-performance needs such as aerospace are met.
Smart Images

Figure CN119952338A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing of metal materials, and in particular to an aluminum-copper alloy wire suitable for arc additive manufacturing and a preparation method thereof. Background Art
[0002] Aluminum-copper alloy has good high and low temperature mechanical properties, good corrosion resistance and welding performance, etc., and is widely used in the manufacture of load-bearing structures such as launch vehicle tanks, transition rings and frame beams. The existing production process of large-scale complex aluminum-copper alloy components mainly includes large-scale ingot casting, homogenization heat treatment, multi-directional forging, punching, horse frame expansion, ring tying, deformation heat treatment, machining, etc. The production process is complicated, the production cycle is long, and the manufacturing cost is high. With the widespread adoption of structure / function / performance integrated design in the new generation of equipment aluminum alloy components, the original split components have become integral, and the consistency requirements of the mechanical properties of the components are getting higher and higher. The existing traditional manufacturing technology can no longer meet its high-efficiency, low-cost and high-performance manufacturing needs.
[0003] Arc additive manufacturing technology is based on a three-dimensional slice model. It uses an arc to melt the wire and deposits it layer by layer along the planned path to prepare a blank component. With a small amount of machining, it can produce large-scale, high-performance, dense and complex components. It is very suitable for the preparation of large-scale complex structures. Relevant literature at home and abroad has verified the feasibility of arc additive manufacturing of aluminum alloy components.
[0004] The premise of arc additive manufacturing technology application is the preparation of high-performance special wires to ensure stable wire feeding, uniform wire droplet transition, uniform wire composition and organization during arc additive forming, and thus ensure the stability of chemical composition, macro-microstructure and mechanical properties of arc additive manufacturing components. Existing aluminum-copper alloy wires are mainly prepared based on traditional welding requirements, with poor chemical composition and organizational uniformity of the wires, and do not consider the effects of complex thermal cycles such as rapid melting / solidification / local remelting / local short-term thermal effects during arc additive manufacturing. Therefore, there is an urgent need to develop special wires specifically for aluminum-copper alloy arc additive.
[0005] The aluminum-copper alloy wires for arc additive manufacturing that have been published so far are mainly made by reducing the content of impurity elements (such as Fe, Si, etc.), reducing interlayer phase precipitation, and reducing plastic anisotropy. By adding trace alloying elements (such as Ti, Zr, etc.), Al3 (Ti, Zr) dispersed particles are formed to refine the α-Al matrix and improve strength performance. However, the proportion of trace alloying elements is not clearly defined, and the comprehensive strengthening effect of trace alloying elements is not comprehensively considered, which can easily lead to excessive content, the formation of intermetallic compounds, and the reduction of the tensile properties of aluminum-copper alloy arc additive forming components. Summary of the invention
[0006] The present invention provides an aluminum-copper alloy wire suitable for arc additive manufacturing and a preparation method thereof. The aluminum-copper alloy wire described in the present invention has a smooth production and processing process, uniform composition and structure, and is suitable for arc additive manufacturing. In the present invention, while regulating the content of trace alloy elements, the purifying grain boundary element Ce is added to further refine the grains and form a dispersedly distributed precipitated phase. After arc additive forming and solution quenching and aging heat treatment, the component structure has fine grains, uniformly distributed strengthening phases, tensile strength greater than 474MPa, yield strength greater than 372MPa, elongation greater than 15.5%, and no plastic anisotropy in the transverse and longitudinal directions.
[0007] In the first aspect, an aluminum-copper alloy wire suitable for arc additive manufacturing is provided, wherein the composition, by mass percentage, is: copper Cu: 5.5-6.5%, manganese Mn: 0.4-0.55%, magnesium Mg: ≤0.02%, zinc Zn: ≤0.1%, vanadium V: 0.3-0.4%, titanium Ti: 0.45-0.6%, zirconium Zr: 0.3-0.45%, cerium Ce: 0.08-0.16%, iron Fe: ≤0.08%, silicon Si: ≤0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0008] In combination with the first aspect, in certain implementations of the first aspect, the composition of the aluminum-copper alloy wire in mass percentage is: copper Cu: 5.5-6%, manganese Mn: 0.5-0.55%, vanadium V: 0.3-0.35%, titanium Ti: 0.45-0.5%, zirconium Zr: 0.3-0.33%, and cerium Ce: 0.08-0.10%.
[0009] In combination with the first aspect, in certain implementations of the first aspect, the composition of the aluminum-copper alloy wire in mass percentage is: copper Cu: 6-6.5%, manganese Mn: 0.4-0.55%, vanadium V: 0.35-0.4%, titanium Ti: 0.5-0.6%, zirconium Zr: 0.33-0.4%, and cerium Ce: 0.1-0.16%.
[0010] In combination with the first aspect, in certain implementations of the first aspect, in terms of mass percentage, Ti:Zr=1.5:1.
[0011] In combination with the first aspect, in certain implementations of the first aspect, the aluminum-copper alloy wire forms an Al3(Ti, Zr) phase and a Ti2Cu phase in the aluminum matrix.
[0012] In combination with the first aspect, in certain implementations of the first aspect, the aluminum-copper alloy wire is used for arc additive manufacturing, and a θ(Al2Cu) structure is formed both in the deposited state and after solid solution failure.
[0013] In a second aspect, a method for preparing an aluminum-copper alloy wire as described in any one of the implementations of the first aspect is provided, comprising:
[0014] (1) Ingredients: pure Al, Al-Cu master alloy, Al-Mn master alloy, Al-Fe master alloy, Al-Ce master alloy, Al-Zr master alloy, Al-Ti master alloy are selected and proportioned according to the composition ratio;
[0015] (2) Alloy smelting: The prepared metal raw materials are subjected to vacuum smelting at a smelting temperature of 750-850°C for 2-3 hours;
[0016] (3) Semi-continuous casting: After the melt is allowed to stand, it is continuously cast at a speed of 200-250 mm / min to obtain an ingot;
[0017] (4) Homogenization treatment: The ingot is placed in an annealing furnace for homogenization treatment, and the temperature is raised to 540-550°C and then kept at this temperature to obtain a homogenized ingot;
[0018] (5) Ingot surface processing: The homogenized ingot is subjected to surface turning processing to remove surface oxide scale and oil stains, and the surface roughness Ra is less than 3.2 to obtain a surface processed ingot;
[0019] (6) Hot extrusion: The surface-processed ingot is subjected to extrusion processing at an extrusion speed of 12 to 14 mm / s to obtain a rod with a diameter of Φ8 to 10 mm;
[0020] (7) Drawing: The prepared rod is subjected to multiple drawing and annealing processes to prepare a wire with a diameter of Φ1.29 mm;
[0021] (8) Scraping treatment: The prepared wire is scraped and peeled with a peeling thickness of 0.06-0.1 mm to remove the surface oxide film to obtain a solid wire;
[0022] (9) Ultrasonic cleaning: The solid wire is subjected to ultrasonic cleaning for 10-15 minutes and then dried.
[0023] In combination with the second aspect, in certain implementations of the second aspect, the cooling rate in step (3) is 100-120K / s.
[0024] In combination with the second aspect, in certain implementations of the second aspect, the standing time in step (3) is 20-30 minutes.
[0025] In combination with the second aspect, in certain implementations of the second aspect, the homogenization time in step (4) is 25-30 hours.
[0026] Compared with the prior art, the solution provided by the present invention includes at least the following beneficial technical effects:
[0027] 1. The present invention further increases the Mn element content, increases the amount of T phase, and refines the α-Al matrix grains. The V element content is increased, further reducing the thermal crack sensitivity of the aluminum-copper alloy, and improving the anti-cracking ability of arc additive manufacturing components and the subsequent solution quenching anti-cracking ability.
[0028] 2. The present invention adjusts the content ratio of Ti and Zr elements, which has obvious effects on refining matrix grains, inhibiting recrystallization and preventing the formation of cracking intergranular phases.
[0029] 3. The present invention adds Ce element, which can promote matrix nucleation and increase the growth stability of spherical interface, and realize Al 13 Fe phase modification improves alloy strength and plasticity.
[0030] 4. After the aluminum-copper alloy wire described in the present invention is subjected to arc additive forming and solution aging heat treatment, the tensile strength of the component is 475-505MPa, the yield strength is 367-394MPa, the elongation is 13.2-16.4%, and there is no plastic anisotropy in the transverse and longitudinal directions, which meets the requirements of aerospace use. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the deposited structure of aluminum-copper alloy arc additive manufacturing. The deposited structure is mainly equiaxed dendrite solidification, the branches are α(Al), and the dendrites are α(Al)+θ(Al2Cu) symbiotic eutectics, and the eutectics are continuous network (gray phase in the figure).
[0032] Figure 2 Arc additive manufacturing solution aging structure of aluminum-copper alloy, with discontinuous distribution of granular θ(Al2Cu) phase (gray) and strip-shaped iron-rich impurity phase (black) between grains, and fine θ(Al2Cu) residual phase in the dendrites. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] The invention provides an aluminum-copper alloy wire suitable for arc additive manufacturing. The wire has the following components by mass percentage: copper Cu: 5.5-6.5%, manganese Mn: 0.4-0.55%, magnesium Mg: ≤0.02%, zinc Zn: ≤0.1%, vanadium V: 0.3-0.4%, titanium Ti: 0.45-0.6%, zirconium Zr: 0.3-0.45%, cerium Ce: 0.08-0.16%, iron Fe: ≤0.08%, silicon Si: ≤0.06%, other single impurity elements (non-alloy): ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0035] In a preferred embodiment, the composition of the aluminum-copper alloy wire suitable for arc additive manufacturing is as follows by mass percentage: copper Cu: 5.5-6%, manganese Mn: 0.5-0.55%, magnesium Mg: ≤0.02%, zinc Zn: ≤0.1%, vanadium V: 0.3-0.35%, titanium Ti: 0.45-0.5%, zirconium Zr: 0.3-0.33%, cerium Ce: 0.08-0.10%, iron Fe: ≤0.08%, silicon Si: ≤0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0036] In a preferred embodiment, the composition of the aluminum-copper alloy wire suitable for arc additive manufacturing is as follows by mass percentage: copper Cu: 6-6.5%, manganese Mn: 0.4-0.55%, magnesium Mg: ≤0.02%, zinc Zn: ≤0.1%, vanadium V: 0.35-0.4%, titanium Ti: 0.5-0.6%, zirconium Zr: 0.33-0.4%, cerium Ce: 0.1-0.16%, iron Fe: ≤0.08%, silicon Si: ≤0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0037] In a preferred embodiment, the mass percentage ratio of Ti:Zr is 1.5:1.
[0038] Cu is an α-Al matrix strengthening element, and precipitates nanoscale θ' phase with Al element after solid solution aging, which improves the strength of the alloy. Mn forms T phase with Al and Cu elements, and disperses and precipitates during solid solution, preventing the recrystallization of aluminum alloy, increasing the recrystallization temperature, and significantly refining the recrystallized grains, which can improve the room temperature and high temperature strength.
[0039] V can prevent the aggregation and coarsening of the precipitated phase at the grain boundary, reduce the thermal crack sensitivity of the aluminum-copper alloy, and improve the room temperature strength and plasticity of the alloy.
[0040] The addition of Ti and Zr to the alloy has two main functions: first, the enrichment of Ti and Zr at the front of the ingot solidification interface can produce a large component supercooling and form fine equiaxed grains. Second, Ti and Zr form Al3 (Ti, Zr) second phase with Al. The second phase particles pin dislocations and matrix grain boundaries, hinder grain boundary migration, and the second phase particles can serve as matrix recrystallization nucleation cores, refine α-Al matrix grains, and improve strength and plasticity. In particular, in the alloy composition, by mass percentage, when Ti: Zr = 1.5: 1, it is ensured that when Ti: Zr = 1: 1, Al3 (Ti, Zr) second phase can be formed to refine grains. At the same time, the remaining Ti can form Ti2Cu phase with Cu, forming dispersed nucleation particles, refining the original α-Al matrix grains, preventing the formation of cracked intergranular phases, and improving strength and plasticity.
[0041] Adding Ce to the alloy will reduce the contact angle between the heterogeneous nucleation particles and the α-Al matrix, promote nucleation, increase the number of grains, and refine the size of the α-Al matrix. In addition, Ce adsorbs on the phase surface, reduces the anisotropy of the solid-liquid interface, reduces the concentration gradient at the solid-liquid interface front and the interface diffusion rate, increases the stability of the spherical interface growth, and realizes Al 13 Fe phase transformation improves alloy strength and plasticity.
[0042] The present invention provides a preparation method for arc additive manufacturing of aluminum-copper alloy wire, which can be prepared according to the following steps:
[0043] (1) Ingredients: pure Al, Al-Cu master alloy, Al-Mn master alloy, Al-Fe master alloy, Al-Ce master alloy, Al-Zr master alloy, Al-Ti master alloy are selected and proportioned according to the composition ratio;
[0044] (2) Alloy smelting: The prepared metal raw materials are subjected to vacuum smelting at a smelting temperature of 750-850°C for 2-3 hours;
[0045] (3) Semi-continuous casting: After the melt is allowed to stand, it is continuously cast at a speed of 200-250 mm / min to obtain an ingot;
[0046] (4) Homogenization treatment: The ingot is placed in an annealing furnace for homogenization treatment, and the temperature is raised to 540-550°C and then kept at this temperature to obtain a homogenized ingot;
[0047] (5) Ingot surface processing: The homogenized ingot is subjected to surface turning processing to remove surface oxide scale and oil stains, and the surface roughness Ra is less than 3.2 to obtain a surface processed ingot;
[0048] (6) Hot extrusion: The surface-processed ingot is subjected to extrusion processing at an extrusion speed of 12 to 14 mm / s to obtain a rod with a diameter of Φ8 to 10 mm;
[0049] (7) Drawing: The prepared rod is subjected to multiple drawing and annealing processes to prepare a wire with a diameter of Φ1.29 mm;
[0050] (8) Scraping treatment: The prepared wire is scraped and peeled with a peeling thickness of 0.06-0.1 mm to remove the surface oxide film to obtain a solid wire;
[0051] (9) Ultrasonic cleaning: The solid wire is subjected to ultrasonic cleaning for 10-15 minutes and then dried.
[0052] Furthermore, in the wire material, in terms of mass percentage, Ti:Zr=1.5:1.
[0053] Furthermore, in step (3), the cooling rate is 100-120 K / s.
[0054] Furthermore, the standing time in step (3) is 20-30 min.
[0055] Furthermore, the homogenization time in step (4) is 25-30 hours.
[0056] The smooth progress of the wire production process is mainly due to the following three points: 1) After smelting, the melt is allowed to stand for 20 to 30 minutes to ensure uniform melt composition. The casting cooling rate is 100 to 120 K / s. The casting process has good heat dissipation, high crystallization efficiency, reduced component segregation, and more uniform chemical composition. At the same time, the rapid solidification of the high-temperature melt can refine the grains, which is beneficial to subsequent extrusion and drawing processing; 2) The homogenization treatment decomposes the non-equilibrium eutectic structure in the ingot in the matrix, and the supersaturated solid solution elements precipitate from the matrix, eliminating casting residual stress and improving the uniformity of casting composition and organization; 3) Wire scraping and ultrasonic cleaning treatments improve the surface quality of the wire and ensure the stability and surface quality of subsequent arc additive forming wire feeding.
[0057] In summary, the present invention realizes arc additive manufacturing of aluminum-copper alloy wires and provides a new high-efficiency, high-performance printing solution for large-scale complex wires. The wires prepared by the above scheme, after arc additive manufacturing and solution aging, have a tensile strength of 474-495 MPa, a yield strength of 372-386 MPa, an elongation of 15.5-18.6%, and no plastic anisotropy in the transverse and longitudinal directions.
[0058] Example 1
[0059] The invention discloses an aluminum-copper alloy wire suitable for arc additive manufacturing and a preparation method thereof. The alloy components, by mass percentage, are copper Cu: 5.5%, manganese Mn: 0.4%, magnesium Mg: 0.02%, zinc Zn: 0.1%, vanadium V: 0.3%, titanium Ti: 0.45%, zirconium Zr: 0.3%, cerium Ce: 0.08%, iron Fe: 0.06%, silicon Si: 0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0060] The production process of aluminum-copper alloy wire is:
[0061] (1) Ingredients: pure Al, Al-Cu master alloy, Al-Mn master alloy, Al-Fe master alloy, Al-Ce master alloy, Al-Zr master alloy, Al-Ti master alloy are selected and proportioned according to the composition ratio; the ingredients are proportioned according to the above composition ratio;
[0062] (2) Alloy smelting: placing the prepared metal raw materials into a vacuum melting furnace for vacuum melting at a vacuum degree of 5 Pa, a melting temperature of 800° C., and a melting time of 2 h to obtain molten raw materials;
[0063] (3) Semi-continuous casting: After the melt is allowed to stand for 20 min, it is cast into a 120 mm Ø cold mold. The cooling rate of the water-cooled mold is 120 K / s and the continuous casting speed is 220 mm / min to obtain an ingot.
[0064] (4) Homogenization treatment: placing the ingot into an annealing furnace for homogenization treatment, heating the ingot to 540°C at a rate of 10°C / min and then maintaining the temperature for 30 hours to obtain a homogenized ingot;
[0065] (5) Ingot surface processing: remove the head and tail of the homogenized ingot, use a lathe to process the ingot into an ingot of 120 mm × 600 mm in diameter, remove the surface oxide scale and oil stains, ensure that the surface roughness of the ingot is Ra < 3.2, and obtain a smooth ingot;
[0066] (6) Hot extrusion processing: The skin-passed ingot is extruded by a hot extruder at an extrusion speed of 12 mm / s to obtain a Φ10 mm rod;
[0067] (7) Drawing: The prepared rod is subjected to 10 drawing and annealing processes to prepare a wire with a diameter of Φ1.29 mm;
[0068] (8) Scraping treatment: The prepared wire is scraped and peeled with a peeling thickness of 0.1 mm to remove the surface oxide film to obtain a solid wire;
[0069] (9) Ultrasonic cleaning: The solid wire is subjected to ultrasonic cleaning for 15 min and then dried to obtain a final product.
[0070] Example 2
[0071] The invention discloses an aluminum-copper alloy wire suitable for arc additive manufacturing and a preparation method thereof. The alloy components, by mass percentage, are copper Cu: 6%, manganese Mn: 0.5%, magnesium Mg: 0.02%, zinc Zn: 0.1%, vanadium V: 0.35%, titanium Ti: 0.5%, zirconium Zr: 0.33%, cerium Ce: 0.1%, iron Fe: 0.06%, silicon Si: 0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0072] The production process of aluminum-copper alloy wire is shown in Example 1, and the final Φ1.2 mm wire can be prepared.
[0073] Example 3
[0074] The invention discloses an aluminum-copper alloy wire suitable for arc additive manufacturing and a preparation method thereof. The alloy components, by mass percentage, are 6.5% copper Cu, 0.55% manganese Mn, 0.02% magnesium Mg, 0.1% zinc Zn, 0.3% vanadium V, 0.6% titanium Ti, 0.45% zirconium Zr, 0.12% cerium Ce, 0.06% iron Fe, 0.06% silicon Si, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0075] The production process of aluminum-copper alloy wire is shown in Example 1, and the final Φ1.2 mm wire can be prepared.
[0076] Comparative Example 1
[0077] The alloy element composition in the comparative example is as follows by mass percentage: copper Cu: 5.8%, manganese Mn: 0.4%, magnesium Mg: 0.02%, zinc Zn: 0.1%, vanadium V: 0.15%, titanium Ti: 0.2%, zirconium Zr: 0.1%, iron Fe: 0.06%, silicon Si: 0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
[0078] The production process of aluminum-copper alloy wire is shown in Example 1, and the final Φ1.2 mm wire can be prepared. The wires with a diameter of 1.2 mm prepared in Comparative Example 1, Example 1, Example 2 and Example 3 are used as raw materials, and arc additive manufacturing equipment is used for component forming and solid solution aging treatment. Figure 1 As shown, the deposited sample of the aluminum-copper alloy arc additive manufacturing in Example 1 presents an α(Al)+θ(Al2Cu) structure. Figure 2 As shown in Table 1, the aluminum-copper alloy solid solution aging (535℃ / 2h / water cooling + 175℃ / 4h / air cooling) sample presents α(Al)+iron-rich impurity phase+fine θ(Al2Cu) residual phase in the crystal. As shown in Table 1, the properties of the formed component are shown in Table 1, the tensile strength is 474-495MPa, the yield strength is 372-386MPa, and the elongation is 15.5-18.6%.
[0079] Table 1 Comparison of tensile properties of aluminum-copper alloy arc additively manufactured components after solution aging
[0080]
[0081] As shown in Table 1, the aluminum-copper alloy wire prepared by the present invention is used to adjust the content of Cu and Mn matrix strengthening elements, regulate the content of Ti and Zr elements to refine the grains while preventing the formation of cracked intergranular phases, and add Ce elements to further refine the grains, improve the strength and plasticity of the component, and eliminate plastic anisotropy. The aluminum-copper alloy wire described in the present invention is more suitable for arc additive manufacturing.
[0082] Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims of the present invention.
Claims
1. A method for arc additive manufacturing of aluminum-copper alloy wire, characterized in that: The composition by mass percentage is: copper Cu: 5.5-6.5%, manganese Mn: 0.4-0.55%, magnesium Mg: ≤0.02%, zinc Zn: ≤0.1%, vanadium V: 0.3-0.4%, titanium Ti: 0.45-0.6%, zirconium Zr: 0.3-0.45%, cerium Ce: 0.08-0.16%, iron Fe: ≤0.08%, silicon Si: ≤0.06%, other single impurity elements: ≤0.05%, other impurity element alloys: ≤0.15%, and the balance is aluminum Al.
2. The aluminum-copper alloy wire according to claim 1, characterized in that: The aluminum-copper alloy wire material has the following components in terms of mass percentage: copper Cu: 5.5-6%, manganese Mn: 0.5-0.55%, vanadium V: 0.3-0.35%, titanium Ti: 0.45-0.5%, zirconium Zr: 0.3-0.33%, and cerium Ce: 0.08-0.10%.
3. The aluminum-copper alloy wire according to claim 1, characterized in that: The aluminum-copper alloy wire material has the following components in mass percentage: copper Cu: 6-6.5%, manganese Mn: 0.4-0.55%, vanadium V: 0.35-0.4%, titanium Ti: 0.5-0.6%, zirconium Zr: 0.33-0.4%, and cerium Ce: 0.1-0.16%.
4. The aluminum-copper alloy wire according to any one of claims 1 to 3, characterized in that: In terms of mass percentage, Ti:Zr=1.5:
1.
5. The aluminum-copper alloy wire according to claim 4, characterized in that: The aluminum-copper alloy wire material has an Al3(Ti, Zr) phase and a Ti2Cu phase formed in an aluminum matrix.
6. The aluminum-copper alloy wire according to any one of claims 1 to 3 and 5, characterized in that: Aluminum-copper alloy wire is used for arc additive manufacturing, and the θ(Al2Cu) structure is formed both in the deposited state and after solid solution failure.
7. A method for preparing an aluminum-copper alloy wire according to any one of claims 1 to 6, characterized in that: include: (1) Ingredients: pure Al, Al-Cu master alloy, Al-Mn master alloy, Al-Fe master alloy, Al-Ce master alloy, Al-Zr master alloy, Al-Ti master alloy are selected and proportioned according to the composition ratio; (2) Alloy smelting: The prepared metal raw materials are subjected to vacuum smelting at a smelting temperature of 750-850°C for 2-3 hours; (3) Semi-continuous casting: After the melt is allowed to stand, it is continuously cast at a speed of 200-250 mm / min to obtain an ingot; (4) Homogenization treatment: The ingot is placed in an annealing furnace for homogenization treatment, and the temperature is raised to 540-550°C and then kept at this temperature to obtain a homogenized ingot; (5) Ingot surface processing: The homogenized ingot is subjected to surface turning processing to remove surface oxide scale and oil stains, and the surface roughness Ra is less than 3.2 to obtain a surface processed ingot; (6) Hot extrusion: The surface-processed ingot is subjected to extrusion processing at an extrusion speed of 12 to 14 mm / s to obtain a rod with a diameter of Φ8 to 10 mm; (7) Drawing: The prepared rod is subjected to multiple drawing and annealing processes to prepare a wire with a diameter of Φ1.29 mm; (8) Scraping treatment: The prepared wire is scraped and peeled with a peeling thickness of 0.06-0.1 mm to remove the surface oxide film to obtain a solid wire; (9) Ultrasonic cleaning: The solid wire is subjected to ultrasonic cleaning for 10-15 minutes and then dried.
8. The aluminum-copper alloy wire according to claim 7, characterized in that: The cooling rate in step (3) is 100-120K / s.
9. The aluminum-copper alloy wire according to claim 7, characterized in that: The standing time in step (3) is 20-30 minutes.
10. The aluminum-copper alloy wire according to claim 7, characterized in that: The homogenization time in step (4) is 25-30 hours.
Citation Information
Patent Citations
Free-cutting aluminum copper alloy extruded bar and preparation method thereof
CN110157965A
Aluminum-copper alloy welding wire prepared from wire additional material
CN111203672A
High-conductivity Al-Fe alloy containing rare earth Ce and preparation method thereof
CN117070806A
Process for coating substrates
EP0497119A1
Aluminum-based welding electrodes
EP3984690A1
Cited By
Preparation method of high-strength aluminum-magnesium-manganese alloy material
CN121674802A